ADDRESSING LEGAL GAPS IN INDONESIA’S INDIVIDUAL LIMITED LIABILITY COMPANY: CHALLENGES AND THE PATH TO REFORM - Irawati, Irawati; Santoso, Budi; Prananingtyas, Paramita (Doctoral of Law Program, Faculty of Law, Universitas Diponegoro, 2025)
The establishment of the Individual Limited Liability Company in Indonesia presents several fundamental issues related to the validity of incorporation documents, ambiguity regarding the pre-approval period, and conceptual inconsistencies between Government Regulation No. 8 of 2021 and the Limited Liability Company Law. One of the main issues is the absence of a notarial deed, which is often the legal basis for establishing a legal entity in Indonesia, creating legal uncertainty for third parties. Additionally, the misalignment in the use of the terms “registration” and “approval” in this regulation contributes to confusion about when the legal entity status of the Individual Limited Liability Company can be obtained. Another issue is the organizational structure of the Individual Limited Liability Company, which combines the functions of shareholder and director in a single individual, eliminating the basic principles of power separation and fiduciary duty that underpin good governance. This also hinders the application of the Piercing the Corporate Veil doctrine and blurs the boundary between the owner and the company itself. The absence of a Supervisory Board in this structure further exacerbates the situation as there is no adequate oversight mechanism. Therefore, an update to Government Regulation No. 8 of 2021 is needed, which includes the obligation for a declaration of establishment before a notary, clarity on the personal responsibility of the founder before approval, and the regulation of a periodic reporting mechanism. In the long term, legislative reforms are necessary to create a new legal entity distinct from the Limited Liability Company Law, considering lessons from other jurisdictions and the values of Pancasila.